The complete mitochondrial genome of Sanghuangporus vaninii Zhehuang-1 (Hymenochaetales, Basidiomycota) - Tingting Song; Fei Xu; Yingyue Shen; Lijun Fan; Weiming Cai (Mitochondrial DNA. Part B. Resources, 2021)
In this study, the complete mitochondrial genome of Sanghuangporus vaninii Zhehuang-1 was determined. Genomic DNA samples individually collected from a population in southeastern China (Qiandaohu, Zhejiang Province, N29°44′24′′, E118°52′48′′) were sequenced with an Illumina NovaSeq 6000. The complete mitochondrial genome was 97,345 bp in length and consisted of 22 protein-coding genes (PCGs), 29 tRNAs, 3 ribosomal RNAs, and a control region. Sanghuangporus vaninii has a mitochondrial gene arrangement that is similar to that of S. sanghuang. Phylogenetic analysis performed using ML methods based on the complete mitogenome sequence showed that S. vaninii is a member of the Polyporaceae. The complete mitogenome sequence provides important data for further study of the Inonotus linteus complex.